Optimization and identification of siderophores produced by Pseudomonas monteilii strain MN759447 and its antagonism toward fungi associated with mortality in Dalbergia sissoo plantation forests - Srivastava, Pragati; Sahgal, Manvika; Sharma, Khanchand; Enshasy, Hesham Ali El; Gafur, Abdul; Alfarraj, Saleh; Ansari, Mohammad Javed; Sayyed, R. Z. (Frontiers in Plant Science, 2022)
Siderophore-positive bacteria in the rhizosphere and bulk soil assist plants by either inhibiting phytopathogen proliferation or increasing plant growth. The bacterial diversity of the shisham forest ecosystem in the Tarai region of the western Himalayas was studied and exploited for siderophore production, keeping in view the large-scale dieback and wilt-induced mortality in Dalbergia sissoo (local name shisham) plantation forests and the importance of soil microbes in tree health. In addition, Pseudomonas, Burkholderia, and Streptomyces were prominent siderophore-positive bacteria in shisham forests. The Pseudomonas species are known for their remarkable siderophore-producing ability. A bacterial siderophore inhibits pathogen growth by rapidly lowering the number of ferric ions in the rhizosphere. Pseudomonas monteilli strain MN759447 was isolated from a D. sissoo plantation forest at the Agroforestry Research Centre in Pantnagar, Uttarakhand(28°58′N 79°25′E/28.97°N 79.41°E). It produces a significant number of siderophore units (80.36 percent of the total). A two-stage optimization of growth factors was attempted in the strain MN759447 for better siderophore recovery. In a first-stage single-factor experiment, amongst the five variables studied, only pH, NH4NO3, and Fe concentration affected siderophore synthesis. Whereas in the second stage, an optimization of pH, NH4NO3, and Fe concentration for improved growth and higher siderophore production was done using a Box Behnken Design in Response Surface Methodology. Two derivatives of pseudomonine, salicyclic acid, and kynurenic acid, were detected as siderophores in XAD-2 purified methanol extract of the strain P. monteilli MN759447 using LCMS. In addition to siderophore production, the P. monteilli MN759447 strain also exhibited a broad range of antagonism against Aspergillus calidoustus (65%), Fusarium oxysporum, Candida albicans (41.66 percent), Talaromyces pinophilus (65%), and Talaromyces verruculosa (65.1%) linked to sissoo mortality. To our knowledge, this is the first report on siderophore-producing bacteria isolated, identified, and characterised from the D. sissoo Roxb. forest habitat. This strain can be a commercial product.